Adrenal Insufficiency Secondary to Septic Shock in a Male Patient with Iatrogenic Cushing's Syndrome: 2 sides of the Same Coin?. (June 2021) - Foppiani, Luca
Cushing's syndrome causes increased morbidity and mortality due to cardiovascular and infectious diseases. Exogenous Cushing's syndrome can render the adrenal glands unable to cope with severe infections and may result in Addisonian crisis, which can be fatal if not properly diagnosed and treated. During hospitalization for disease exacerbation, a man on chronic glucocorticoid therapy for Crohn's disease and Cushingoid features developed polymicrobial septic shock together with hypotension that was unresponsive to fluids. On suspicion of relative adrenal insufficiency (cortisol levels were "inadequately" normal), intravenous hydrocortisone was started; norepinephrine was also required to normalize blood pressure. Following clinical improvement, oral cortisone acetate was started. On discharge, he was instructed on how to manage stressful events by increasing oral glucocorticoid treatment or starting a parenteral formulation, if required. Chronic glucocorticoid therapy can cause severe side-effects; in addition, hypoadrenalism can occur in critical illnesses (eg, severe infections). Prompt recognition and proper therapy of this condition can be life-saving.